Stellar signatures of AGN-jet-triggered star formation - Dugan, Zachary; Gaibler, Volker (The astrophysical journal, 2014)
To investigate feedback between relativistic jets emanating from active galactic nuclei and the stellar population of the host galaxy, we analyze the long-term evolution of the orbits of the stars formed in the galaxy-scale simulations by Gaibler et al. of jets in massive, gas-rich galaxies at z ∼ 2-3. We find strong, jet-induced differences in the resulting stellar populations of galaxies that host relativistic jets and galaxies that do not, including correlations in stellar locations, velocities, and ages. Jets are found to generate distributions of increased radial and vertical velocities that persist long enough to effectively augment the stellar structure of the host. The jets cause the formation of bow shocks that move out through the disk, generating rings of star formation within the disk. The bow shock often accelerates pockets of gas in which stars form, yielding populations of stars with significant radial and vertical velocities, some of which have large enough velocities to escape the galaxy. These stellar population signatures can serve to identify past jet activity as well as jet-induced star formation.